A beacon in the dark: COVID-19 course in CVID patients from two European countries: Different approaches, similar outcomes - Milito, Cinzia; Firinu, Davide; Bez, Patrick; Villa, Annalisa; Punziano, Alessandra; Lagnese, Gianluca; Costanzo, Giulia; van Leeuwen, Leanne P. M.; Piazza, Beatrice; Deiana, Carla Maria; d’Ippolito, Giancarlo; Del Giacco, Stefano Renato; et al. (Frontiers in Immunology, 2023)
Background: CVID patients present an increased risk of prolonged SARS-CoV-2 infection and re-infection and a higher COVID-19-related morbidity and mortality compared to the general population. Since 2021, different therapeutic and prophylactic strategies have been employed in vulnerable groups (vaccination, SARS-CoV-2 monoclonal antibodies and antivirals). The impact of treatments over the last 2 years has not been explored in international studies considering the emergence of viral variants and different management between countries. Methods: a multicenter retrospective/prospective real-life study comparing the prevalence and outcomes of SARS-CoV-2 infection between a CVID cohort from four Italian centers (IT-C) and one cohort from the Netherlands (NL-C), recruiting 773 patients. Results: 329 of 773 CVID patients were found positive for SARS-CoV-2 infection between March 1st, 2020 and September 1st 2022. The proportion of CVID patients infected was comparable in both national sub-cohorts. During all waves, chronic lung disease, “complicated” phenotype, chronic immunosuppressive treatment and cardiovascular co-morbidities impacted on hospitalization, whereas risk factors for mortality were older age, chronic lung disease, and bacterial superinfections. IT-C patients were significantly more often treated, both with antivirals and mAbs, than NL-C patients. Outpatient treatment, available only in Italy, started from the Delta wave. Despite this, no significant difference was found for COVID-19 severity between the two cohorts . However, pooling together specific SARS-CoV-2 outpatient treatments (mAbs and antivirals) , we found a significant effect on the risk of hospitalization starting from Delta wave. Vaccination with ≥ 3 doses shortened RT-PCR positivity, with an additional effect only in patients receiving antivirals. Conclusions: The two sub-cohorts had similar COVID-19 outcomes despite different treatment approaches. This points out that specific treatment should now be reserved for selected subgroups of CVID patients, based on pre-existing conditions.